2014
DOI: 10.1016/j.neures.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Wnt/β-catenin signaling in the development of neuropathic pain

Abstract: Despite tremendous research effort in the field, our current understanding of the molecular mechanisms underlying neuropathic pain is still incomplete. In the present study, our objective was to elucidate the involvement of the Wnt/β-catenin signaling pathway in the development of neuropathic pain. We showed that Wnt/β-catenin signaling is activated in the spinal cord dorsal horn after partial sciatic nerve ligation (PSL). Expression of Wnt3a, a prototypic Wnt ligand that activates the Wnt/β-catenin pathway, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…Previous studies highlight the vital role of spinal β-catenin in neuropathic pain 16 24 25. Neuropathic pain upregulates spinal β-catenin, and the blockade of Wnt/β-catenin signals attenuates the induction of neuropathic pain 24. In the present study, we have demonstrated that both PRF-DRG and PRF-SN could downregulate the expression of β-catenin, indicating the involvement of β-catenin signal pathway in PRF’s analgesic action.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies highlight the vital role of spinal β-catenin in neuropathic pain 16 24 25. Neuropathic pain upregulates spinal β-catenin, and the blockade of Wnt/β-catenin signals attenuates the induction of neuropathic pain 24. In the present study, we have demonstrated that both PRF-DRG and PRF-SN could downregulate the expression of β-catenin, indicating the involvement of β-catenin signal pathway in PRF’s analgesic action.…”
Section: Discussionsupporting
confidence: 59%
“…6). Wnt signaling has been shown to influence spinal cord dorsal horn and dorsal root ganglia patterning during the pathogenesis and the development of neuropathic pain (Itokazu et al 2014;Zhang et al 2013). Based on these, we speculate that TCF4 may be involved in the maintenance of neuropathic pain through mediating the activation of Wnt/β-catenin pathway following peripheral nerve injury in rats.…”
Section: Activation Of Wnt/β-catenin Signaling In the Dorsal Root Ganmentioning
confidence: 77%
“…Previous studies have shown that Wnt/β-catenin signaling was activated in the spinal cord in the partial sciatic nerve ligation (PSL) model (Itokazu et al 2014). Nevertheless, it is little known how TCF4 plays an important Fig.…”
Section: Activation Of Wnt/β-catenin Signaling In the Dorsal Root Ganmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF has also been implicated in the etiology of diverse types of neurological disorders (Harte-Hargrove et al 2013), such as depression (Manosso et al 2015; Stuke et al 2012), schizophrenia (Notaras et al 2015; Reinhart et al 2015; Zhang et al 2016), Alzheimer’s disease (AD) (Phillips et al 1991; Tapia-Arancibia et al 2008), Huntington’s disease (HD) (Borrell-Pages et al 2006), and Parkinson’s disease (PD) (L’Episcopo et al 2014). Remarkably, many recent studies have shown that BDNF is emerging as a particularly important player in neuropathic pain (Coull et al 2005; Inoue 2009; Itokazu et al 2014). Chronic pain is a common neurological comorbidity of HIV-1 infection, but the etiological cause and its underlying mechanism remain elusive (Yuan et al 2014).…”
Section: Instructionmentioning
confidence: 99%